Assessment of Function after Free Tissue Transfer to the Lower Extremity for Chronic Wounds Using the Lower Extremity Functional Scale - Falola, Reuben A.; Lakhiani, Chrisovalantis; Green, Jocelyn; Patil, Siya; Jackson, Brandon; Bratescu, Rachel; Anghel, Ersilia; Steinberg, John S.; Kim, Paul J.; Attinger, Christopher E.; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2018)
Background Free tissue transfer is one option for preservation of form and function in the native limb, in the setting of soft tissue paucity. However, the data on patient functionality after microvascular intervention is inconsistently reported. The Lower Extremity Function Scale (LEFS) measures patient-reported difficulty in carrying out 20 physical activities, on a Likert scale, the sum of which correlates with descriptive functional stages of 1–5. We assess limb functionality in this cohort of microvascular patients using the LEFS survey.Methods A retrospective chart review was conducted at a single academic medical center of 101 consecutive free flaps, from 2011 to 2016. Of the flaps that met inclusion criteria, 39 had completed LEFS surveys. Mean LEFS scores were calculated, and the effects of risk factors such as diabetes, age, and smoking status were analyzed.Results The mean LEFS score after free tissue transfer was 50.3 (SD ± 21.1), with a mean follow up survey time of 3.0 years (SD ± 1.3). The score correlated with Stage 4 function, or "independent community ambulation,” and age was the only demographic factor associated with decreased functionality in this group. This is compared with mean LEFS score of 43.1 (SD ± 18.4) in cohort of 55 below knee amputations (BKAs), and 38.3 (SD ± 14.9) in 28 above knee amputations (AKAs), both correlating with Stage 3 function: “limited community ambulation.”Conclusions Functional outcomes scores such as the LEFS demonstrate that patients can obtain an adequate level of functionality for independent community activity after free tissue transfer, although functional improvement diminishes with age.
Keywords: microvascular surgery; lower extremity functional scale; chronic wound